-6(x-2)+4(8x-12)=68

Simple and best practice solution for -6(x-2)+4(8x-12)=68 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x-2)+4(8x-12)=68 equation:


Simplifying
-6(x + -2) + 4(8x + -12) = 68

Reorder the terms:
-6(-2 + x) + 4(8x + -12) = 68
(-2 * -6 + x * -6) + 4(8x + -12) = 68
(12 + -6x) + 4(8x + -12) = 68

Reorder the terms:
12 + -6x + 4(-12 + 8x) = 68
12 + -6x + (-12 * 4 + 8x * 4) = 68
12 + -6x + (-48 + 32x) = 68

Reorder the terms:
12 + -48 + -6x + 32x = 68

Combine like terms: 12 + -48 = -36
-36 + -6x + 32x = 68

Combine like terms: -6x + 32x = 26x
-36 + 26x = 68

Solving
-36 + 26x = 68

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 26x = 68 + 36

Combine like terms: -36 + 36 = 0
0 + 26x = 68 + 36
26x = 68 + 36

Combine like terms: 68 + 36 = 104
26x = 104

Divide each side by '26'.
x = 4

Simplifying
x = 4

See similar equations:

| 6ln(3x)=12 | | -6(x-2)-4(8x-12)=68 | | 3x-2=7x+8 | | 4(-6+x)=5x+1/4 | | h=4a-3 | | 1/6-18/12 | | 7-3(5t-7)=67 | | 5x^2y^4-80x^4y^2=0 | | 1=23*t+2-1-2+1-23*t+2*t-1*t | | 23*t+2-1-2+1-23*t+2*t-1*t=1 | | 2w^2-5w-88=0 | | 2x-6+5=11 | | 3x-1-4=1 | | (-5y^3/8y^4)*(64y^6/25y) | | 3056890000-15000000x=3000000 | | 2n^3-32n=0 | | 1/3(9k-6)=7 | | 3a-4b=14 | | 2sinX+X=0 | | sinx+x=0 | | 6/2/3=18/N | | 830+840+380+380= | | 3/8m=9 | | 13.95x+8=15.95x | | D=175+70t | | D=175+70 | | D=175+-70 | | -9(t+4)=36 | | 27+3y-6=11y-9-2y | | D=175+-70t | | x+18+4x=-30-4x-33 | | 24y=14y-8 |

Equations solver categories